2018
DOI: 10.1186/s13033-018-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

“My bitterness is deeper than the ocean”: understanding internalized stigma from the perspectives of persons with schizophrenia and their family caregivers

Abstract: BackgroundIt is estimated that 8 million of the Chinese adult population had a diagnosis of schizophrenia. Stigma associated with mental illness, which is pervasive in the Chinese cultural context, impacts both persons with schizophrenia and their family caregivers. However, a review of the literature found a dearth of research that explored internalized stigma from the perspectives of both patients and their caregivers.MethodsWe integrated data from standardized scales and narratives from semi-structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 66 publications
2
46
0
3
Order By: Relevance
“…My thought is that wherever we live, we wanted to keep good relationships with our neighbors. (Wong et al )Being too open isn’t good either, but I do think functional openness is important. (van der Sanden et al 2014)Because I’ve been incredibly selective, as to who I choose and discuss this with…I got a lot of empathy… people that care about me, they are concerned about me…this is because I’ve been very, very, very careful about who I discuss this with.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…My thought is that wherever we live, we wanted to keep good relationships with our neighbors. (Wong et al )Being too open isn’t good either, but I do think functional openness is important. (van der Sanden et al 2014)Because I’ve been incredibly selective, as to who I choose and discuss this with…I got a lot of empathy… people that care about me, they are concerned about me…this is because I’ve been very, very, very careful about who I discuss this with.…”
Section: Resultsmentioning
confidence: 98%
“…The internalization of stigma was identified among family members in some studies. Participants indicated that stigma experiences provoked self‐discrimination and sometimes caused them to internalize the negative stereotypes associated with mental illness (Buizza et al ; Gonzalez‐Torres et al ; Muhlbauer ; Wong et al ). A few spoke about feeling bad about themselves or having ‘lost self‐esteem’ (Koschorke et al, ).
Before I had a competitive disposition (I considered myself to be stronger than others).
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations